Large scale self-assembly of SnSe nanosheets prepared by the hot-injection method for photodetector and capacitor applications. (June 2019) - Zhong, Yujia; Zhang, Li; Sun, Mengxing; Wang, Min; Chen, Wenduo; Lin, Shuyuan; Xie, Dan; Zhu, Hongwei
Abstract: As a semiconductor with layered structure, tin selenide (SnSe) is both a photoelectric material and a thermoelectric material. A large number of solution synthetic methods have been developed to synthesize SnSe. However, the fundamental properties of SnSe prepared by solution methods remain largely unexplored, and the applications of SnSe are also limited. In the present study, SnSe nanosheet (SnSeNS) with homogeneous lateral dimension was successfully prepared by hot-injection method. We assessed the fundamental photoelectrical properties of SnSeNS and exploited it in two applications: photodetector and capacitor. A self-assembly technique based on the Marangoni effect was exploited to obtain large scale homogeneous macro films on different substrates. Based on this assembly method, we constructed graphene/SnSe/graphene vertical structure and exploited it as a photodetector. The responsivity of SnSe was 38 mA W −1 . The area-specific capacitance of pure SnSeNS reached 5.56 mF cm −2 . Furthermore, a flexible capacitor based on SnSeNS was developed for potential wearable applications. Graphical abstract: SnSe nanosheets (SnSeNS) with good crystallinity and uniform lateral dimension were prepared by hot-injection method. The fundamental photoelectrical properties, including resistance, mobility, band gap and work function of SnSeNS were assessed. A self-assembly method based on the Marangoni effect was exploited to form large scale films for photodetector and supercapacitor applications.Image 1 Highlights: SnSe nanosheets with good crystallinity and uniform lateral dimension are prepared by hot-injection. The photoelectrical properties (resistance, mobility, band gap and work function) of SnSe nanosheets are assessed. A self-assembly method based on the Marangoni effect is exploited to form homogeneous films. Photodetectors and supercapacitors are assembled based on SnSe films.